An assessment of demand for Internet services at the community of Nkowankowa in the Greater Tzaneen Municipality (GTM) in Limpopo Province - Mashapu, Mosupje Moses (My University, 2011)
Internet services can make a significant contribution towards the development of people both in the urban and rural areas. The study is focused on the demand for internet services in the community of Nkowankowa in the Greater Tzaneen Municipality (GTM) in Limpopo province. Internet services bring multiple opportunities such as information, e-mails, games, shopping, banking, and real time news. The study examined the nature of demand for internet infrastructure and services in the area. The study further explored strategies that may be cost-effective and affordable to internet users and to recommend strategies through which the municipality can improve internet service delivery. The use of internet services was also examined (i.e., what are internet services needed for)? To understand these challenges and obtain in-depth information, both qualitative and quantitative research approach were used. The study population consisted of business owners (SMMEs), schoolmaster, students, and management in the municipal management committee, internet café owners, computer home users, police management and health management in Nkowakowa community in the Greater Tzaneen Municipality, selected through a purposive sampling method. These management workers are main role players in the use of internet services. A small sample of 40 respondents was selected based on the potential or likelihood that the respondents had same knowledge and interest in internet services. The researcher has selected the relative small sample because of the limited time frame. The findings reveal that Nkowankowa has a high shortage of internet infrastructure such as telephony. The entire Section C does not have a landline infrastructure and the only possibility is mobile connection, which is expensive. The internet cafés stand at 2 against the population of 30515 (Greater Tzaneen Municipality IDP: 2005-2006:12). The community depends on those two internet cafés. Learned individuals and business have afforded to connect. Others depend on internet services from their institutions, work place, and internet cafes. Challenges of the infrastructure unavailability such as telephony have a negative impact on utilization. It was recommended that the Municipality should partner with NGOs and community based organizations to deliver internet and related services to the community.
Thesis (M.Dev) --University of Limpopo, 2011
Keywords: Internet services; 004.6780968; Internet users